IMPLEMENTASI METODE NAÏVE BAYES CLASSIFIER DALAM SISTEM PAKAR DEFISIENSI NUTRISI PADA BALITA - Helson Mandala Putra; LM Fid Aksara; Rahmat Ramadhan (Informatics Engineering Department of Halu Oleo University, 2016)
Nutrition deficiency is one of the problems experienced by most children under five years old in Indonesia. This problem appear because the lack of knowledge from parents about nutrition which needed by their children. Regarding with such problem, the researcher then made a diagnose system which provided the information about nutrition deficiency of the children to the people, in order to prevent any problem of nutrition deficiency per se. The system was an expert system of nutrition deficiency using Naïve Bayes Classifier method. This method was developed from Bayes Theorem, where the value of probability from an object was classified based of specific requirements. Some research showed that Naïve Bayes Classifier was the best among other classification methods, so that the researcher employed this method in the research. In the system, the indication of nutrition deficiency was determined based on antropometri table including the data about height, weight, and age as well as additional indication to make a specific result. Then the data of 20 patients were examined using confusion matrix method. The result showed that the system was 90% accurate. Indeed, it proved that the system could be very helpful to make a classification for nutrition deficiency and it could be applied in any of local government clinic and hospital. Keywords— Antropometri, Deficiency, Naïve Bayes